Our early results of carotis endarterectomy with no shunt and primary closure method - Tamtekin, Burak; Ersoy, Güler Gülsen; Dal, İsmail (MediHealth Academy, 2023)
Aims: Carotid artery disease is one of the most important causes of stroke. If left untreated, it causes serious mortality and morbidity. The gold standard treatment for carotid artery stenosis is carotid endarterectomy. The use of shunt, primary or patch closure of the arteriotomy varies according to clinical experience. In this article, we present the results of carotid endarterectomy performed with no shunt and primary closure method. Methods: Thirty cases who underwent carotid endarterectomy in our clinic between April 2021 and April 2022 were analyzed retrospectively. All patients underwent selective carotid surgery. All surgeries were performed with the same technique and under general anesthesia. The patients were evaluated in terms of demographic characteristics, operation time, cross-clamp time, mortality, morbidity, and hospital stay. Results: The clinical data of the early follow-up in the first month postoperatively were evaluated. Six (20%) of the patients were female and 24 (80%) were male. All of the males were active smokers. The mean age was 71.1 (min:65-max:82). Twenty five patients had a history of coronary artery disease. The mean cross-clamp time was 9.1 (±0.8) minutes. All surgeries were performed without using shunts. In all patients, primary closure was performed without the use of arterotomy grafts. Conclusion: As an early morbidity, dysphagia was detected in 1 patient. This symptom disappeared at follow-up at 1 month. No early mortality was observed in any patient at 1-month follow-up. With increasing experience, carotid endarterectomy operations can be performed safely with no shunt and primary closure method. Our early surgical results are consistent with the literature.
Keywords: 3. Good health